2020
DOI: 10.1111/ijcs.12574
|View full text |Cite
|
Sign up to set email alerts
|

Fast‐food addiction and anti‐consumption behaviour: The moderating role of consumer social responsibility

Abstract: This study aims to understand the drivers of fast‐food addiction and the role of consumer social responsibility (CSR) on the relationship between fast‐food addiction and anti‐consumption. Due to growing health concerns, an increasing number of consumers have been avoiding the consumption of fast food. Based on a sample of 539 respondents, all pertaining to generation Y in Pakistan, this study tests a model including addiction and anti‐consumption behaviour. Empirical results provide strong evidence that indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 80 publications
(127 reference statements)
2
75
0
Order By: Relevance
“…Similarly, addictive food consumption and disordered eating share several psychological constructs including reward dysfunction, craving, emotion dysregulation, and impulsivity (Schulte, Grilo, & Gearhardt, 2016). A model testing study, using the theory of planned behavior (TPB) and the selfcongruity theory, indicated that individual factors (e.g., emotional states, psychopathological problems) and sociodemographic factors (e.g., gender, age, education level) should be associated with food addiction (Farah & Shahzad, 2020).…”
Section: Factors Associated With Addictive Food Consumptionmentioning
confidence: 99%
“…Similarly, addictive food consumption and disordered eating share several psychological constructs including reward dysfunction, craving, emotion dysregulation, and impulsivity (Schulte, Grilo, & Gearhardt, 2016). A model testing study, using the theory of planned behavior (TPB) and the selfcongruity theory, indicated that individual factors (e.g., emotional states, psychopathological problems) and sociodemographic factors (e.g., gender, age, education level) should be associated with food addiction (Farah & Shahzad, 2020).…”
Section: Factors Associated With Addictive Food Consumptionmentioning
confidence: 99%
“…To select the sample of the Basque Country retailer, a combination of convenience sampling and the snowball sampling procedure was used. While this study acknowledges the limitations related to the use of such data collection methods, these methodologies are used and accepted in the academic literature (Farah & Shahzad, 2020) when there are time and cost constraints and when it is necessary for a study to investigate a certain group. Moreover, these sampling methods were addressed by following Raschke, Krishen, Kachroo, and Maheshwari's (2013) recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…All constructs and variables were tested for both convergent validity and discriminant validity. For reliability purposes, "measures of composite reliability (CR) and the average variance extracted (AVE) values were considered" (Farah & Shahzad, 2020). To accept the convergent validity of all variables, "the cut-off value of the CR for all variables must be above .60, and the AVE values above .50" (Sekaran & Bougie, 2013, p. 160).…”
Section: Measurement Modelmentioning
confidence: 99%